AN ANALYSIS OF JUDGES JURIDICAL JUDEX FACTIE WHO UNCHECKING THE FACTS AND TRIAL EVIDENCE IN MONEY LAUNDERING: THE CASE STUDY OF JUDGE'S DECISION NO. 383 K/PID.SUS/2017 - Maulana, Ahmad Afandi (jfpublisher, 2022)
Money laundering is a series of actions that was done to hide or disguise the original process of criminal act (illegal money) from government or other competent authority. it is a crime that has characteristic of transnational, money laundering has an impact on economic stability of a country. This research is normative legal research, which include as a type of research that examines statutory rule or norm from certain legal force. This research supported by constitution No. 8/2010 concerning on the Prevention and Eradication of Crime for Money Laundering. This research began with the decision of East Jakarta District Court No. 605/Pid.B/2009/PN.Jkt. Tim which stated that the defendant Sudjatmiko was found not guilty of committing money laundering, however after the cassation applicant/public prosecutor was filed a cassation request, an appeal was filed. This decision was accepted by the Panel of Judges for Supreme Court and sentenced the defendant Sudjatmiko to 6 (six) years in prison (Decision No. 383K/Pid.Sus/2017). Based on the research analysis, it turned out that judex factie did not apply the law of evidence as intended in articles 183, 184 to 189 on The Code of Criminal Procedure.